Role of Rasayana Prophylaxis in Degenerative Disorders: A Comprehensive Review (International Journal of Ayurveda and Pharma Research, 2025)
Degenerative disorders are characterized by progressive tissue and organ deterioration and pose significant challenges to health and quality of life, especially in ageing populations. The degenerative disorders, including osteoarthritis, Alzheimer’s disease, cardiovascular diseases, and osteoporosis, are characterized by the progressive deterioration in the structure and function of tissues and organs due to oxidative stress, biological ageing, and chronic inflammation. Through its Rasayana therapy, which is the core concept and prophylactic measures, Ayurveda offers comprehensive and holistic strategies for managing and preventing these conditions. Derived from the Sanskrit words Rasa and Ayana, Rasayana emphasizes enhancing overall health by nourishing tissues, enhancing immunity, balancing the body’s Doshas and delaying the ageing process. Through its antioxidant, anti-inflammatory and adaptogenic properties, which mitigate oxidative damage, regulate immune responses and improve cellular repair mechanisms. Prophylactic use of Rasayana not only prevents the onset of degenerative disorders but also delays their progression by improving cellular adaptability, slowing age-related decline and enhancing metabolism. This article explores the application of Rasayana and prophylaxis in managing and preventing degenerative disorders, emphasizing herbal, dietary and lifestyle interventions. It also highlights key Rasayana formulations, such as Ashwagandha (Withania somnifera), Amalaki (Emblica officinalis), Guduchi (Tinospora cordifolia), Brahmi (Bacopa monnieri), etc., and their roles in reducing inflammation, enhancing adaptability against age-related decline, and supporting tissue regeneration. Incorporating Rasayana and prophylaxis into the contemporary healthcare system offers a sustainable and effective pathway to address the rising burden of degenerative disorders.